CEPHALOSPORIN DERIVATIVES (1974)
1348737 Cephalosporins TAKEDA YAKUHIN KOGYO KK 31 May 1972 [31 May 1971] 25417/72 Addition to 1304647 Heading C2A Novel cephalosporin compounds having the Formula (I) and salts and esters thereof, wherein R1 is an acyl group and each of R2 and R3, which may be the same or different, is a hydrogen atom or a C 1 -C 4 alkyl group, a carboxyl group, an amino group, a dimethylamino group or a hydroxymethyl group, or R2 and R3 together form a group of formula -NH-CH=N-, are prepared by either (1) reacting a 7-acylamino-3- acetoxymethylcephalosporanic acid or its salt or ester in which the acyl group is R1, with a compound of formula or a salt or ester thereof; or (2) reacting a 7- aminocephalosporanic acid of formula or a salt or ester thereof, with an acid R1COOH or an N-acylating derivative thereof. Any amino groups present in the reactants may be protected by conventional N-protecting groups. Pharmaceutical compositions having antibiotic activity against gram-positive and negative micro-organisms comprise a cephalosporin (I) or its salt or ester together with a pharmaceutically acceptable carrier.